Improving nitrogen use and yield with stay-green phenotypes in wheat - Derkx, Adinda Pieterdina (2013)
Wheat grain yield is strongly related to nitrogen (N) fertiliser input, a major cost factor and potential environmental pollutant. Much of the grain N requirement is met by N remobilisation from the canopy. Unfortunately, a consequence is canopy senescence and decreased photosynthetic capacity, reducing carbon available for grain-filling. One approach to achieve both higher N use efficiency and grain yield would be to extend the duration of photosynthesis using delayed leaf senescence “stay-green” phenotypes.